Application of quantum-inspired evolutionary algorithm in the analysis of near infrared diffuse transmission spectroscopy of apples - LI Jun-liang; WANG Cong-qing (浙江大学学报. 农业与生命科学版)
To study the application of quantum-inspired evolutionary algorithm (QEA) in the analysis of near infrared (NIR) diffuse transmission spectroscopy of apples, first, spectroscopy regions were preselected by using the backward interval partial least squares (BiPLS). Second, the variables were selected with QEA, and QEA-PLS model was built. Meanwhile, genetic algorithm (GA) -PLS model was developed to contrast with QEA-PLS model. After running GA and QEA 10 times separately, the two best models were chosen from the 10 GA-PLS models and the 10 QEA-PLS models. The results showed that the GA-PLS model had 110 variables, with RMSEC (root mean standard error of calibration) of 0.582 0, RMSEP (root mean standard error of prediction) of 0.612 3, but the QEA-PLS model had 194 variables, with RMSEC of 0.492 7, RMSEP of 0.526 0. It is concluded that QEA can be used in the analysis of NIR diffuse transmission spectroscopy of apples and enhance the precision of model. Compared to GA, search capability of QEA is better.